Disruptive Innovation in Hospitality Human Resource - Joshi, Basant P. (Journal of Tourism and Hospitality Education, 2018)
In this 21st century, where all the organizational activities are transforming into a digital technology base, the disruption in any business cannot be imagined without adapting a technological break through. Technological disruption in HR may cause a robotic service experience for the customers, especially in the hospitality industry because if the human resource component is replaced with the technology, for e.g. a meal service in the restaurant if replaced with a robotic machine or a robot, the human touch component of that experience will not be realized by the customer hence the service in a long run becomes mechanistic. The innovation theory seems to be more relevant to any product or a service but when we talk about human resource, it is neither a product nor a service. The term Human Resource is used to the people those who work for the organization and also the department who is responsible for managing the required resources for the employees to facilitate their job. The term Human Resource was first coined in the year 1960 when people realized the value of labor relation, motivation, behavior and productivity. Journal of Tourism and Hospitality Education 8 (2018) 1-29